The Effect Of Social Media Marketing Grab Medan On Brand Equity With E-Satisfaction And E-Loyalty As Intervening Variables - Shubita Devi Harahap, Dharma; Wahyuningtyas, Ratri; Firli, Anisah (International Journal of Science, Technology & Management, 2023)
The purpose of this study was to find out how much influence social media marketing carried out by Grab Medan has on brand equity through e-satisfaction and e-loyalty. This research is included in quantitative research with data collection methods in the form of questionnaires. The data analysis technique used is the Structural Equation Model (SEM) using the SmartPLS program. The statistical test results show that Grab Medan's social media marketing has a positive and significant effect on Grab's brand equity. This means that marketing carried out by Grab Medan online on its Instagram account can influence or increase brand equity at Grab Medan. The better the marketing done by Grab Medan on its Instagram account, the brand equity of Grab Medan will increase or get better. However, the increase in brand equity is also influenced by e-satisfaction and e-loyalty. E-Loyalty has the greatest influence in increasing brand equity, satisfaction and convenience for consumers in obtaining information and good service from Grab can form high e-loyalty from its users. The effect of e-satisfaction can be seen from the ease of accessing information, a good experience when accessing information, and consumer interest in the content provided by Grab Medan which can increase the e-satisfaction of its users.